Peneraapan Moddel Kooperatif Tipe Think-Pair-Share Untuk menyempurnakan Partisipasi Siswa Pada Mata Pelajaran PPKN Di Kelas - Handayani, Soniya; Anderson, Irzal; Sariani, Dona (Citizenship Education, Faculty of Education, Jambi University, 2021)
Abstract This research is motivated by several obstacles in the implementation of learning, namely the low participation of students, besides the fact that teachers use learning methods commonly applied in the classroom is conventional learning which tends to minimize student involvement and teachers are more active. Based on the results of the study, it was shown that in the process of implementing the Think Pair Share Cooperative Learning Model in Civics subjects, student participation increased. This success criterion is 75% or more of the 100% percentage range. This success can be proven in the first cycle before the application of the Think Pair Share Cooperative Learning Model, the student participation was only at 45.9% in the low category, after applying the model at the end of the first cycle the percentage of students increased to 60.5% in the sufficient category. In the second cycle the percentage of student participation increased again to 65.8% in the good category, but had not reached the desired target and in the third cycle the student participation increased from the second cycle, which was 79.1% in the good category.